Problem to solution; from mammalian skin grafts to renal allograft rejection: a tale of 66 years of evolution of our understanding - Dhrolia, Murtaza; Ahmad, Aasim (Journal of the Pakistan Medical Association, 2023)
The first successful kidney transplant was done in 1954, and it remains the best option for those with failed kidneys. However, the recipient’s immune system remains the most formidable barrier to transplantation, leading to rejection. Rejection continues to be the most important reason of graft malfunction and chronic renal allograft dysfunction and remains a challenge to date for successful transplant survival. The current narrative review was planned to find the best possible solution to the problem from among the different solutions presented in literature related to allograft rejection since 1954. Key Words: Evolution, Renal transplantation, Allograft rejection, Immunosuppressant.